Sistem Pembelajaran Budaya Sumatera Utara Berbasis Android Development Tools - Naely Farkhatin; Thomas Afrizal; Arif Ubaidillah (Universitas Indraprasta PGRI Jakarta, 2018)
Culture is a life aspect covering all behaviors, beliefs, ways to behave and results of human activities typical of society or certain community. The culture includes traditional house, traditional attire, traditional song and traditional ceremony. North Sumatra is a province that has varied culture in many fields. Therefore, the researcher interviews many informants, especially historians or traditional figures in North Sumatra to study its culture. With the increasingly rapid development of technology, the researcher initiates the creation of an application to introduce the culture of North Sumatra using android Development Tools. It is expected that this application can be an interactive and interesting learning medium for society and tourists who want to learn the culture of North Sumatra.